Low temperature in situ formation of cobalt in silicon nitride toward functional nitride nanocomposites. Issue 16 (28th January 2021) - Tada, Shotaro; Mallmann, Maira Debarba; Takagi, Haruna; Iihama, Junya; Asakuma, Norifumi; Asaka, Toru; Daiko, Yusuke; Honda, Sawao; Nishihora, Rafael Kenji; Machado, Ricardo Antonio Francisco; Bernard, Samuel; Iwamoto, Yuji
Abstract : A proposed reaction scheme for in situ controlled low-temperature formation of metallic-Co at the early stage of pyrolysis of perhydropolysilazane (PHPS) coordinated with CoCI2 . Abstract : This work highlights the first demonstration of a low-temperature in situ formation of Co nanocrystallites embedded within an amorphous silicon nitride matrix through careful control of the chemistry behind material design using perhydropolysilazane (PHPS) as a Si3 N4 precursor further coordinated with CoCl2 and ammonia as a pyrolysis atmosphere. The Co nucleation was allowed to proceed at temperatures as low as 400 °C via thermal decomposition of Co2 N pre-formed in situ by the reaction of CoCl2 with the Si centers of PHPS at the early stage of pyrolysis (220–350 °C).